Søndbjergstenens tosprogede tekst - Jensen, Jørgen (Kirkehistoriske Samlinger, 1993)
A bilingual text written in runes, from the second half of the twelfth century demonstrates a combination of a knowledge of the Danish heritage with an active interest in new intellectual developments taking place in the South. The inscription is found on a runic stone, which is now used as a cornerstone in the tower of the church of Søndbjerg in north west Jutland, but may once have been part of a stone altar-table. The inscription is in Danish and Latin, and reads: »Jakop uulæ, Skialm gurôæ ubi ara ibi okolus«. The Danish text can be translated »Jacob ordered, Skialm acted«, and is selfexplanatory. The Latin text is unknown in literature, but follows the well-known pattern demonstrated in the sentence »ubi crux, ibi lux«. The text could also have been inspired by Psalm 33, 18-19 »Behold, the eye of the Lord is upon them that fear him ...«. Although the Vulgate has »eyes«, in the plural, Jerome’s translation after the Hebrew has the singular »eye«. Psalters providing alternate versions were quite common in the twelfth century: for example, the Eadwine Psalter from England had all three ofJerome’s versions of the Psalms, with glosses in English and Anglo-Norman. There were close connections between England and western Jutland in the twelfth century. Although the author of the Søndbjerg text is unknown, the use of »ara« for the Christian altar, rather than the more usual »altare«, suggests a sophisticated knowledge of Latin. Such use of classical terms taken from Roman writers is characteristic of the »twelfth century renaissance«, and suggests that the author had been in touch, directly or indirectly, with the mainstream of twelfth century intellectual developments. Close connections are known to have existed between Denmark and the monastery of St. Geneviève in Paris, where the author himself, or his acquaintances, may have studied. A possible candidate for nomination as the author of the inscription is magister Nicolaus, from the Augustinian monastery at Vestervig, 25 km from Søndbjerg. In 1196 as Court Chaplain was in touch with people who had studied in Paris.